The effect of online pornography on pornography motivation, sexual arousal and gratification and its link to tendencies towards internet-pornography-viewing disorder IPD - Ma’rof, Aini Azeqa; Abdullah, Haslinda; Hamsan, Hanina Halimatusaadiah; Kamaruddin, Mohd Shahrul (Human Resource Management Academic Research Society, 2021)
There has been a recent surge of research about behavioral addictions; some of them focus specifically on internet pornography addiction. However, despite all efforts, it is still unable to identify when engaging in this behavior becomes pathological. Thus, this research was conducted to identify the effects of online pornography consumption between pornography motivation, sexual arousal and gratification on the tendencies towards Internet Pornography-Viewing Disorder (IPD). A total of 202 online pornography users were involved in this study through snowball sampling technique based on an online questionnaire that were distributed to online channels such as e-mail lists, and social media websites (e.g., Twitter, Facebook and WhatsApp) that specifically targeted to online pornography users. Results shows that there was significant positive correlation of watching pornography on all sexual attitudes on the tendencies towards IPD. Meanwhile, having sexual arousal while viewing online pornography reported as the main indicator to IPD. The results showed effects of watching online pornography on pornography motivation, sexual arousal and gratification which can be considered having reinforcing effects for the users. Thus, the results are in line with theoretical assumptions on IPD’s development, in which reinforcement received by Internet-pornography use is related to cue-reactivity and craving reactions.